Predicting Different Types of Intimate Partner Aggression Perpetration: The Roles of Problem Alcohol Use and Distress Tolerance. Issue 13 (July 2022) - Kline, Nora K.; Cabrera, Korine B.; Reed, Kathleen M. Palm
Intimate partner aggression (IPA) victimization and substance use have been well established as risk factors for IPA perpetration (Leonard, 2005 ;Sprunger et al., 2015 ). Recent research has identified a negative association between distress tolerance and physical and psychological IPA perpetration, specifically in males in substance use treatment (Shorey et al., 2017 ). Research examining the interplay of problem substance use, distress tolerance, and other forms of IPA (i.e., sexual coercion, controlling behaviors) in non-clinical samples is limited. The present analysis aimed to examine the potential moderating effect of distress tolerance on problem alcohol use and four types of IPA perpetration (physical assault, psychological aggression, sexual coercion, and controlling behaviors) in a diverse, national sample ( N = 323; 44.3% female; 52.9% sexual minority; age M = 33.61 years, SD = 8.71). Results showed that alcohol use and distress tolerance had differing influences on each IPA perpetration type. In line with hypotheses, distress tolerance significantly moderated the relationship between problem alcohol use and two forms of IPA (physical assault and controlling behaviors); this relationship was stronger for individuals with low levels of distress tolerance. Significant interaction effects did not emerge for psychological aggression or sexual coercion. Findings suggest that treatment strategies that focus specifically on increasing distress tolerance may be effective in reducing alcohol-facilitated IPA perpetration involving physical assault and controlling behaviors.